1999
DOI: 10.1517/13543784.8.7.1063
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of nesiritide (recombinant b-type natriuretic peptide) in the treatment of heart failure

Abstract: This review outlines the chemical properties, pharmacology and clinical trials data which support the development of nesiritide (synthetic human B-type natriuretic peptide, or hBNP) as a therapeutic agent for patients with decompensated congestive heart failure. Nesiritide is a 32-amino acid peptide, structurally identical to endogenous hBNP. Clinical trials with single bolus, repeated boluses and sustained infusions of nesiritide have demonstrated prompt, significant and sustained reductions in pulmonary capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…Recombinant BNP itself (nesiritide or Natricor) is used therapeutically in HF patient to ameliorate acute symptoms such as dyspnea and reduced cardiac output [117,118]. Treatment with these recombinant forms of BNP results in an inhibition of the renin-angiotensin system and aldosterone release, which promotes diuretic and vasodilatory effects.…”
Section: Usefulness Of Current Bnp and Nt-probnp Assays In Patients Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant BNP itself (nesiritide or Natricor) is used therapeutically in HF patient to ameliorate acute symptoms such as dyspnea and reduced cardiac output [117,118]. Treatment with these recombinant forms of BNP results in an inhibition of the renin-angiotensin system and aldosterone release, which promotes diuretic and vasodilatory effects.…”
Section: Usefulness Of Current Bnp and Nt-probnp Assays In Patients Rmentioning
confidence: 99%
“…It has been shown that NTproBNP does not respond dynamically over the course of a nesiritide infusion, probably because of its longer half-life [119]. Nesiritide has an extremely short half-life of 18 minutes [118]. Thus, although it has been argued that NTproBNP may be advantageous because nesiritide may obscure BNP levels, it is unlikely due to the half-life of the treatment.…”
Section: Usefulness Of Current Bnp and Nt-probnp Assays In Patients Rmentioning
confidence: 99%
“…Nesiritide (hBNP) represents a new class of drugs with vasodilating properties; it has no inotropic properties, does not inhibit the phosphodiesterase pathway, is not associated with increased cyclic adenosine monophosphate, and works independently of ß-adrenergic receptors [20,21]. Several studies have shown that an infusion of nesiritide, with a half-life of approximately 18 min [21], is associated with decreased pulmonary capillary wedge pressure (PCWP), sys-temic vascular resistance (SVR), and pulmonary artery pressure (PAP), as well as increased cardiac index (CI), stroke volume index (SVI), and natriuresis [12,20]. Nesiritide has demonstrated some potential for decreasing plasma aldosterone [22] without activating the sympathetic system [23].…”
Section: Heart Failurementioning
confidence: 99%
“…Initial trials involving nesiritide utilized bolus doses [20,21,31] or continuous infusions [12,[32][33][34]. The bolus studies utilized sequentially increasing doses in 27 patients [20], repetitive boluses of the same dose in 29 patients [31], and repetitive doses comparing 60 patients with and without ACE inhibitors [21].…”
Section: Clinical Trials Of Nesiritidementioning
confidence: 99%
See 1 more Smart Citation